2021
DOI: 10.3389/fonc.2021.738080
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tumor–Stroma Ratio on the Prognosis of Colorectal Cancer: A Systematic Review

Abstract: BackgroundIt is critical to develop a reliable and cost-effective prognostic tool for colorectal cancer (CRC) stratification and treatment optimization. Tumor–stroma ratio (TSR) may be a promising indicator of poor prognosis in CRC patients. As a result, we conducted a systematic review on the predictive value of TSR in CRC.MethodsThis study was carried out according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guideline. An electronic search was completed using commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…By examining TSR of colon carcinoma, the authors divided these tumors into "stroma-rich" and "stroma-poor" groups by a cutoff TSR value of 50% and illustrated a profound prognostic signi cance between the two groups. Since its rst appearance, the use of TSR has gained popularity with many subsequent illustrating its effect on survival outcomes [13,14]. The application of TSR concept in tumor prognostication has spread to other solid tumors such as ovarian carcinoma, cervical squamous cell carcinoma, hepatocellular carcinoma, non-small cell lung cancer, nasopharyngeal squamous cell carcinoma, pancreatic ductal adenocarcinoma, and invasive bladder cancer [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…By examining TSR of colon carcinoma, the authors divided these tumors into "stroma-rich" and "stroma-poor" groups by a cutoff TSR value of 50% and illustrated a profound prognostic signi cance between the two groups. Since its rst appearance, the use of TSR has gained popularity with many subsequent illustrating its effect on survival outcomes [13,14]. The application of TSR concept in tumor prognostication has spread to other solid tumors such as ovarian carcinoma, cervical squamous cell carcinoma, hepatocellular carcinoma, non-small cell lung cancer, nasopharyngeal squamous cell carcinoma, pancreatic ductal adenocarcinoma, and invasive bladder cancer [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…SARIFA-status is assessed using routine Haematoxylin & Eosin (H&E) stained tissue sections from CRC resection specimens. Another known H&E based prognostic biomarker in CRC [9] , [10] , [11] , [12] , [13] , [14] is the intratumoural stroma content. Whilst SARIFA-status can only be assessed in tissue regions where tumour cells have the opportunity to get into contact with fat cells (especially in the submucosa and subserosa/adventitia), the intratumoural stroma content can be measured in all regions of the tumour including in material from the luminal tumour surface e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies highlighting the relevance of tumour-stroma ratio/tumour cell proportion/tumour cell density/proportion of tumour (PoT) for prognosis prediction in CRC patients: High intra-tumour stroma content measured using different methods has been shown to predict poor prognosis in several different CRC patient cohorts [9] , [10] , [11] , [12] , [13] , [14] , [15] and other tumour types. Moreover, it has been suggested that tumour stroma is actively involved in CRC development and progression, and that disruption of the tumour-stroma interaction may inhibit tumour progression and metastasis formation [16] .…”
Section: Introductionmentioning
confidence: 99%
“…In general a stromal content of more than around 50% is assessed by the different authors, although different cut-off values are also used for very-high stroma tumors. Both optical and automated reading of stroma is used [3] TSR is not yet adopted in clinical guidelines, and we consider its adoption early. In our study we tried to confirm or dismiss the hypothesis that a simple, unselective optical measurement of stroma quantity at the invasion front is an easy-to-use and strong prognostic tool.…”
Section: Introductionmentioning
confidence: 99%